The effects of plyometric type neuromuscular training on postural control performance of male team basketball players - Asadi, A.; Saez de Villarreal, E.; Arazi, H. (The Journal of Strength and Conditioning Research, 2015)
Anterior cruciate ligament injuries are common in basketball athletes; common preventive programs for decreasing these injures may be enhancing postural control (PC) or balance with plyometric training. This study investigated the efficiency of plyometric training program within basketball practice to improve PC performance in young basketball players. Sixteen players were recruited and assigned either to a plyometric + basketball training group (PT) or basketball training group (BT). All players trained twice per week, but the PT + BT followed a 6-week plyometric program implemented within basketball practice, whereas the BT followed regular practice. The star excursion balance test (SEBT) at 8 directions (anterior, A; anteromedial, AM; anterolateral, AL; medial, M; lateral, L; posterior, P; posteromedial, PM; and posterolateral, PL) was measured before and after the 6-week period. The PT group induced significant improvement (p = 0.05) and small to moderate effect size in the SEBT (A = 0.95, AM = 0.62, AL = 0.61, M = 0.36, L = 0.47, P = 0.27, PM = 0.25, PL = 0.24). No significant improvements were found in the BT group. Also, there were significant differences between groups in all directions except PM and PL. An integrated plyometric program within the regular basketball practice can lead to significant improvements in SEBT and consequently PC. It can be recommended that strength and conditioning professionals use PT to enhance the athletes' joint awareness and PC to reduce possible future injuries in the lower extremity.